Monomethine cyanine probes for visualization of cellular RNA by fluorescence microscopy. (13th July 2021) - Aristova, Daria; Kosach, Viktoriia; Chernii, Svitlana; Slominsky, Yuriy; Balanda, Anatoliy; Filonenko, Valeriy; Yarmoluk, Sergiy; Rotaru, Alexandru; Özkan, Hülya Gizem; Mokhir, Andriy; Kovalska, Vladyslava
Abstract: We have studied spectral-luminescent properties of the monomethine cyanine dyes both in their free states and in the presence of either double-stranded deoxyribonucleic acids (dsDNAs) or single-stranded ribonucleic acids (RNAs). The dyes possess low fluorescence intensity in an unbound state, which is increased up to 479 times in the presence of the nucleic acids. In the presence of RNAs, the fluorescence intensity increase was stronger than that observed in the presence of dsDNA. Next, we have performed staining of live and fixed cells by all prepared dyes. The dyes proved to be cell and nuclear membrane permeant. They are photostable and brightly stain RNA-containing organelles in both live and fixed cells. The colocalization confirmed the specific nucleoli staining with anti-Ki-67 antibodies. The RNA digestion experiment has confirmed the selectivity of the dyes toward intracellular RNA. Based on the obtained results, we can conclude that the investigated monomethine cyanine dyes are useful fluorescent probes for the visualization of intracellular RNA and RNA-containing organelles such as nucleoli by using fluorescence microscopy.